Does Coffee Intake Reduce Postoperative Ileus After Laparoscopic Elective Colorectal Surgery? A Prospective, Randomized Controlled Study: The Coffee Study. Issue 8 (August 2019) - Hasler-Gehrer, Simone; Linecker, Michael; Keerl, Andreas; Slieker, Juliette; Descloux, Alexandre; Rosenberg, Robert; Seifert, Burkhardt; Nocito, Antonio
Abstract : BACKGROUND: Postoperative ileus after colorectal surgery is a frequent problem that significantly prolongs hospital stay and increases perioperative costs. OBJECTIVE: The aim was to evaluate the effect of standardized coffee intake on postoperative bowel movement after elective laparoscopic colorectal resection. DESIGN: This is a prospective randomized controlled trial that was conducted between September 2014 and December 2016. SETTINGS: This study was performed in a public cantonal hospital in Switzerland with accreditation for colon and rectum cancer surgery. PATIENTS: Patients who underwent elective colorectal surgery were included. INTERVENTIONS: Patients were randomly assigned either to the intervention group receiving coffee or the control group receiving tea. A total of 150 mL of the respective beverage was drunk 3 times per day every postoperative day until discharge. MAIN OUTCOME MEASURES: The primary end point was time to first bowel movement. Secondary end points included the use of laxative, insertion of a nasogastric tube, length of hospital stay, and postoperative complications. RESULTS: A total of 115 patients were randomly assigned: 56 were allocated to the coffee group and 59 to the tea group. After coffee intake, the first bowel movement occurred after a median of 65.2 hours versus 74.1 hours in the control group (intention-to-treat analysis; p = 0.008). The HR for earlier first bowel movement after coffee intake was 1.67 ( p = 0.009). In the per-protocol analysis, hospital stay was shorter in the coffee group (6 d in the coffee group vs 7 d in the tea group; p = 0.043). LIMITATIONS: The rate of protocol violation, mostly coffee consumption in the tea arm, was relatively high, even if patients were clearly instructed not to consume coffee if they were in the tea arm. CONCLUSIONS: Coffee intake after elective laparoscopic colorectal resection leads to faster recovery of bowel function. Therefore, coffee intake represents a simple and effective strategy to prevent postoperative ileus. SeeVideo Abstract athttp://links.lww.com/DCR/A955 . TRIAL REGISTRATION: clinicaltrials.gov identifier: NCT02469441.